The Significance of Ocular Findings in the Diagnosis of Fabry’s Disease - Cem Özgönül; Osman Melih Ceylan; Volkan Hürmeriç; Fazıl Cüneyt Erdurman; Üzeyir Erdem (Türk Oftalmoloji Dergisi, 2011)
Fabry’s disease is an X-linked, inherited disorder caused by a deficiency of the enzyme alfa-galactosidase A and characterized by progressive accumulation of glycosphingolipids within several tissues and organs, including the eye. Ocular findings of Fabry’s disease are cornea verticillata, conjunctival vascular changes, retinal vessel tortuosity and cataract. We report the clinical and confocal microscopic findings of cornea verticillata observed in a patient who was diagnosed as Fabry’s disease. (Turk J Oph thal mol 2011; 41: 414-6)